2012
DOI: 10.15407/ujpe57.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Вплив Співадсорбованих Атомів Стронцію На Поверхневу Дифузію У Субмоношарових Плівках Літію На Грані (112) Вольфраму

Abstract: Методом сканувальної контактно-потенціальної мікроскопії досліджено поверхневу дифузію літію у субмоношарових співадсорбованих плівкахLi–Sr на атомно-анізотропній грані (112) вольфраму. Мета роботи – дослідження впливу сильно зв'язаних і менш рухливих адатомів (Sr) на кінетику дифузії більш рухливих адатомів (Li). Встановлено, що адатоми стронцію сильно пригнічують дифузію літію. Одержано концентраційні залежності хімічних коефіцієнтів дифузії, енергії активації і передекспонентного множника у рівнянні Арреніу… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the case of attractive lateral interaction, the set of 2D structures will be significantly poorer [9,[18][19][20]. Previously, we studied surface diffusion in real experiments [21][22][23]. It was shown that the concentration distributions of adatoms in the presence of concentration gradients demonstrate the dependence of diffusion coefficients on the concentration of adatoms.…”
mentioning
confidence: 99%
“…In the case of attractive lateral interaction, the set of 2D structures will be significantly poorer [9,[18][19][20]. Previously, we studied surface diffusion in real experiments [21][22][23]. It was shown that the concentration distributions of adatoms in the presence of concentration gradients demonstrate the dependence of diffusion coefficients on the concentration of adatoms.…”
mentioning
confidence: 99%